Development of a one-year-old asian dummy model for finite element prediction of injury in automotive crash - Jalaluddin, Mai Nursherida (2017)
Child crash dummies are commonly used for safety performance evaluations in vehicle crash tests. To analyze detail injuries in various body parts of a child, material modellling are useful, and provide information that cannot be obtained by crash dummies. To date, finite element (FE) modelling was gradually used to investigate child head dynamic response under drop test impact conditions. However, due to ethical reasons, none of developed one-year-old (1YO) head FE model was found to be quantitatively validated against child cadaver test at similar age group. In the present research, a biofidelic FE model of 1YO head with fontanel, neck, and chest were developed to investigate child head dynamic response under drop impact conditions, neck pendulum analysis and frontal thorax impact analysis. The model was developed by using both deformable and rigid body materials, which consists of about 108,331 elements, and a morphing method within LS-Prepost software was used to morph the geometry. In order to determine the biofidelity of the skin and muscle of 1YO FE model with viscoelastic materials, the material properties need to be modelled accurately. There are three different cases of material modelling considered in this study. It is based on their level of difficulty and accuracy in the analysis to ensure that the desired accuracy level in the stress singularity analysis is attained. Case 1: The viscoelastic shear modulus is modelled as the standard linear solid model and Poisson’s ratio is constant. Case 2: Poisson’s ratio and Viscoelastic shear modulus are modelled as the standard linear solid model. Case 3: Both the Poisson’s ratio and Viscoelastic shear modulus are modelled as the Wiechert Model. Using recently published material property data, the child skull, skin and scalp of the 1YO FE model was developed to study the response in head drop tests, neck pendulum tests and frontal thorax tests. The test procedures followed are in accordance to the specifications from National Highway Traffic Safety Administration (NHTSA) Appendix E Part 572 Subpart 152 (for head, neck and thorax analysis) and ECE-R44 (for thorax analysis). The characteristics of the 1YO child FE model proved to be close to the Anthropometric Test Device (ATD) and child threshold corridor. For the head impact, a good correlation in terms of accelerations (g) between child cadaver experiment and simulation were obtained. For neck pendulum test and frontal thorax analysis, comparison of results indicated that the FE model showed fairly good biofidelic behaviour in both dynamic responses. The viscoelastic properties for Case-3 are determined using the best fit curve technique. From the results, it shows that the experimental curve of the viscoelastic shear modulus of human skin and muscle and the fitting curve were in accordance to the model described in Case-3. Even though this 1YO FE model has several limitations in areas such as the anatomical shapes of a child, this model can be useful tool to examine the behaviour of child impacts, which may be difficult to predict by using existing ATD dummy with its stiff material properties.